2001
DOI: 10.1152/ajpgi.2001.280.1.g32
|View full text |Cite
|
Sign up to set email alerts
|

Inducible and neuronal nitric oxide synthase involvement in lipopolysaccharide-induced sphincteric dysfunction

Abstract: We examined the effect of endotoxin lipopolysaccharide (LPS) on the basal tone and on the effects of different stimuli and agonists and transcriptional and translational expression of nitric oxide (NO) synthase (NOS) isozymes in the lower esophageal sphincter (LES), pyloric sphincter (PS), and internal anal sphincter (IAS). NO release was also examined before and after LPS. LPS caused a dose-dependent fall in the basal tone and augmentation of the relaxation caused by nonadrenergic, noncholinergic (NANC) nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 30 publications
2
52
0
2
Order By: Relevance
“…The authors concluded that exogenous NO has a prejunctional inhibitory effect on the nitrergic component of the NANC response, resulting from a down-regulation of nNOS (De Man et al, 1995). Studies of the effect of the endotoxin lipopolysaccharide on the GI tract have associated delay in gastric emptying and intestinal transit with increased expression of inducible NOS (iNOS) (Takakura et al, 1997;Fan et al, 2001;De Winter et al, 2002). The substantial concentrations of NO which can be generated by iNOS are known to autoinhibit the constitutive forms of NOS (cNOS), which may result in a condition in which iNOS is overexpressed, while cNOS is concurrently inhibited (Schwartz et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that exogenous NO has a prejunctional inhibitory effect on the nitrergic component of the NANC response, resulting from a down-regulation of nNOS (De Man et al, 1995). Studies of the effect of the endotoxin lipopolysaccharide on the GI tract have associated delay in gastric emptying and intestinal transit with increased expression of inducible NOS (iNOS) (Takakura et al, 1997;Fan et al, 2001;De Winter et al, 2002). The substantial concentrations of NO which can be generated by iNOS are known to autoinhibit the constitutive forms of NOS (cNOS), which may result in a condition in which iNOS is overexpressed, while cNOS is concurrently inhibited (Schwartz et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that LPS causes delayed gastric emptying (6,7), intestinal dysmotility (7,8) and sphincteric dysfunction (9), thus unravelling its interaction with enteric nerves. The precise mechanisms behind these acute LPS-induced motor effects are, however, as yet largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal dysmotility under septic conditions accompanies other forms of morbidity, and results in prolonged hospitalization, increased medical costs, and an increase in mortality rate. Although several pathogenic mechanisms including local inflammation, cytokines, such as tumor necrosis factor (TNF) or interleukin-1 (IL-1), and an increase in nitric oxide (NO), have been proposed for motility disorders under sepsis (4,5,18,30), the central mechanisms of gastrointestinal dysmotility under these conditions have not been elucidated. Interstitial cells of Cajal (ICCs), which mediate input from the enteric motor nervous system to smooth muscle, are the pacemaker cells in the gastrointestinal tract (9).…”
mentioning
confidence: 99%